THE EFFECT OF METFORMIN MONOTHERAPY ON BIOCHEMICAL PARAMETERS ASSOCIATED WITH DIABETES MELLITUS, KIDNEY, CARDIAC, LIVER, THYROID, AND REPRODUCTIVE ORGAN FUNCTIONS IN PRE- AND POST-MENOPAUSE WOMEN WITH TYPE 2 DIABETES MELLITUS - Kumar D, Arun; R, Arivazhagan; G, Sudhandiran; R, Sangeetha; S, Swaminathan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aim of this study was to find out the alterations in biochemical parameters associated with the functioning of kidney, cardiac, liver, thyroid, and reproductive organs in pre- and post-menopause Type 2 diabetes mellitus (T2DM) women treated with metformin monotherapy (MMT) and to select a set of biochemical tests as routine to evaluate the functions of the above organs at regular intervals of time based on the levels of various biochemical parameters during a period of 1 year at 6 and 12 months. Method: A total of 100 T2DM patients (50 pre- and 50 post-menopause women) who visited Apollo Speciality Hospitals Vanagaram, Sugar Clinic, and who were on treatment with MMT and 100 (50 pre- and 50 post-menopause age-matched non-diabetic women) were enrolled for this study. Fully automated analyzers and reagents and controls were used for all the assays to ensure the validity of the results obtained. GraphPad online calculator was used to calculate t and p values. Results: MMT for menopause women with T2DM had improved the diabetic parameters, and the levels of fasting plasma glucose (FPG), postprandial plasma glucose (PPPG), and glycosylated hemoglobin (HbA1c) have dropped from 179.48 mg/dL, 270.8 mg/dL, and 8.75% at diagnosis to 135.36, 199.45, and 7.05, respectively, after 12 months of MMT. In the case of post-menopause, the corresponding levels were 180.6, 263.2, and 8.85 to 133.79, 189.06, and 6.68%, respectively, and all the five organ functions were also not altered as the parameters tested for each organ function returned to normal. The drop in all the parameters levels was significant compared to the levels at diagnosis and the p values ranged from <0.01 to<0.0001. Conclusion: Metformin treatment has shown very good improvement in the progressive reductions in the levels of FPG, PPPG, and HbA1c as well as maintaining the functions of kidney, cardiac, liver, thyroid, and reproductive organs to near normal as per the associations of these organ-specific parameters before and after 6 and 12 months of MMT.